2023
DOI: 10.1097/pra.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Cognitive Symptoms Following Intranasal Esketamine Administration in Patients With Chronic Treatment-resistant Depression: A 12-Week Case Series

Abstract: Background: Cognitive symptoms are a core feature of depressive disorders, interfere with full functional recovery and are prominent in patients with treatment-resistant depression (TRD), particularly in severe chronic cases. Intranasal (IN) esketamine was recently approved for the treatment of TRD; however, its effects on cognitive symptoms are unclear. In this article, we describe cognitive changes in 8 patients with chronic TRD who were treated with IN administration of esketamine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The execution of TMT involves several cognitive functions as well and depends on both prefrontal and non-frontal brain region activity, although there are some differences between the two parts of the task [ 79 , 80 ]. Indeed, it has been reported that TMT-A scores can be considered a measure of attention and speed that mainly relies on visual scanning and graphomotor and visuomotor processing speed, while working memory, inhibition control, or set-switching abilities seem to be more specifically implicated in TMT-B performance [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The execution of TMT involves several cognitive functions as well and depends on both prefrontal and non-frontal brain region activity, although there are some differences between the two parts of the task [ 79 , 80 ]. Indeed, it has been reported that TMT-A scores can be considered a measure of attention and speed that mainly relies on visual scanning and graphomotor and visuomotor processing speed, while working memory, inhibition control, or set-switching abilities seem to be more specifically implicated in TMT-B performance [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the brain-derived neurotrophic factor (BDNF) has been reported among the underlying mechanisms of the association between suicidality and depression [63]. Besides the inhibition of NMDA receptors, ketamine and esketamine can exert favorable effects on neuroinflammation through the modulation of BDNF and other intracellular proteins like the mechanistic target of rapamycin complex 1 (mTORC1) [18]. Indeed, an anti-inflammatory effect has been reported for both compounds with a potential enhancement of their anti-depressive properties [64].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of treatments is mainly based on objective criteria and clinicians' evaluation; however, including patients' self-rated, lived experience on changes in their symptomatology might be useful to understand the perceived helpfulness of therapies and to fill the knowledge gap about treatment outcomes [14,15]. Preliminary data focusing on clinician-rated specific symptoms and psychopathological dimensions reported beneficial effects of ESK-NS on anxiety, cognition, and physical correlates, as well as on anhedonia and suicidality in TRD patients [2,[16][17][18]. However, little evidence is available on the viewpoint of patients with TRD receiving esketamine, and it has been investigated through audio interviews [19] and self-administered questionnaires assessing cognition, quality of life, and functional outcomes [18,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation